2016
DOI: 10.1111/bjet.12514
|View full text |Cite
|
Sign up to set email alerts
|

Teachers’ knowledge in content, pedagogy and technology integration: A comparative analysis between teachers in Saudi Arabia and United States

Abstract: Teachers’ technological pedagogical content knowledge (TPACK) involves an awareness of instructional approaches, methods, and knowledge of building on technology to enhance students’ learning. The purpose of this study was to evaluate the TPACK of teachers in Saudi Arabia and USA, and then describe the factors affecting teachers’ TPACK through an analysis of covariance that incorporates age, teaching experience, and education level as covariates, and the seven levels of TPACK as dependent variables. Difference… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 11 publications
2
19
0
Order By: Relevance
“…Our results show that teaching experience had a negative influence as more experience is acquired; therefore, Hypothesis 3c must be rejected. Previous studies are in agreement [30,31], where teachers with shorter experience tend to have a higher level of ICT and disability knowledge. Thus, the support from the Government bodies, the use of adequate material and personnel resources, the improvement of the teacher's qualifications, and the coordination with education agents would improve the use of these devices in the classroom and enable greater inclusion of students with disabilities.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Our results show that teaching experience had a negative influence as more experience is acquired; therefore, Hypothesis 3c must be rejected. Previous studies are in agreement [30,31], where teachers with shorter experience tend to have a higher level of ICT and disability knowledge. Thus, the support from the Government bodies, the use of adequate material and personnel resources, the improvement of the teacher's qualifications, and the coordination with education agents would improve the use of these devices in the classroom and enable greater inclusion of students with disabilities.…”
Section: Discussionsupporting
confidence: 73%
“…This is in line with previous research conducted in the international context such as those mentioned above [16][17][18][19], where this low level of training is also evident. These deficiencies in the teaching competence seem to be modulated by factors such as the gender [27,28] or even the age of the teachers, which seems to determine their level of competence in this field [29,30]. The years of teaching experience are also revealed as a determining factor in the level of ICTs skills, where teachers with less teaching experience tend to show a higher level of competence for the incorporation of ICTs [31,32].…”
Section: Introductionmentioning
confidence: 99%
“…In this sense, in both cases the younger teachers indicated having more knowledge. Previous research has already confirmed these findings (Alqurashi et al ., ; Gudmundsdottir & Hatlevik, ). This could be explained by the younger teachers being closer to the end of their studies, and the recent addition to the curriculum of training elements on the use of ICT with people with disabilities.…”
Section: Discussionmentioning
confidence: 99%
“…Also, Cabero and Martín (2014) argue that younger teachers have greater knowledge, and also, Alqurashi et al (2017), Gudmundsdottir and Hatlevik (2017) indicate that the recently-qualified (recent graduates) feel more confident about integrating this technology.…”
Section: Introductionmentioning
confidence: 99%
“…Firstly, two main methods to measure participants' TPACK, including via self-report and via performance (e.g., Kafyulilo, Fisser, Pieters, & Voogt, 2015;Maeng, Mulvey, Smetana, & Bell, 2013). The distinction between them is that TPACK can reflect in one end as knowledge (via self-report) (e.g., Abbitt, 2011;Alqurashi, Gokbel, & Carbonara, 2017), and in the other end as competence or performance that can be observed (via performance) (e.g., Kafyulilo, Fisser, Pieters, & Voogt, 2015;Maeng, Mulvey, Smetana, & Bell, 2013).…”
Section: Tpack Frameworkmentioning
confidence: 99%